2012
DOI: 10.1007/s10616-012-9495-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chicken-origin cells on adaptation of a low pathogenic influenza virus

Abstract: Understanding the growth dynamics of influenza viruses is an essential step in virus replication and cell-adaptation. The aim of this study was to elucidate the growth kinetic of a low pathogenic avian influenza H9N2 subtype in chicken embryo fibroblast (CEF) and chicken tracheal epithelial (CTE) cells during consecutive passages. An egg-adapted H9N2 virus was seeded into both cell culture systems. The amount of infectious virus released into the cell culture supernatants at interval times post-infection were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…IRF7, is activated by TLR-dependent signaling pathways and it regulates type I IFN responses [44]. NF-κB is a vital transcription factor that regulates genes responsible for a variety of immune response [42].…”
Section: Discussionmentioning
confidence: 99%
“…IRF7, is activated by TLR-dependent signaling pathways and it regulates type I IFN responses [44]. NF-κB is a vital transcription factor that regulates genes responsible for a variety of immune response [42].…”
Section: Discussionmentioning
confidence: 99%
“…If the embryo died, the allantoic fluid and internal organs were tested for waterfowl parvovirus antigens by LA and IFA. Duck embryo fibroblasts (DEF) cells were prepared from 11-day-old Cherry Valley duck embryos as described previously [19]. DEF monolayer cell cultures were inoculated with allantoic fluid, and cultures were incubated at 37°C in 5 % CO 2 for 7 days, followed by three further passages in DEF.…”
Section: Virus Isolationmentioning
confidence: 99%
“…It has been shown that difference among cell tropism may be due to different amounts of endogenous trypsin-like enzyme present in the cells that subsequently activate the cleavability of the HA. It was demonstrated that recent H9N2 viruses possess di-and tribasic HA cleavage sites RXXR (the case of our variants) or RSK/RR motifs (Aamir et al, 2007;Xu et al, 2007) which are activated by type II transmembrane serine proteases (TTSPs) (Baron et al, 2013), HAT (human airway trypsin-like protease), TMPRSS2 (transmembrane protease, serine S1 member 2), expressed in the human airway epithelium, the gastrointestinal, and urogenital tracts (Bottcher et al, 2013) and VAP and chTMPRSS13 in the chicken tracheal epithelium cells (Bertram et al, 2010a(Bertram et al, , 2010bShahsavandi et al, 2013). Likewise, another cellular protease, matriptase, which is expressed in the epithelial cells of most tissues but with higher expression levels in the kidney (Baron et al, 2013), was able to support proteolytic activation of H9N2 viruses showing cleavage site motifs R-S-S-R or R-S-R-R, but not those containing a single arginine or motif A-S-R-R.…”
Section: Discussionmentioning
confidence: 99%